2022
DOI: 10.1016/j.jcmgh.2021.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing STK25 Signaling Suppresses the Development of Hepatocellular Carcinoma Through Targeting Metabolic, Inflammatory, and Pro-Oncogenic Pathways

Abstract: We provide evidence that antagonizing STK25 activity hinders the development of hepatocellular carcinoma, which is one of the most fatal cancers. This study provides an impetus for further analysis of STK25 as a therapeutic target in liver cancer. CONCLUSIONS:This study provides evidence that antagonizing STK25 signaling hinders the development of NASH-related HCC and provides an impetus for further analysis of STK25 as a therapeutic target for NASH-induced HCC treatment in human beings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…[ 95 ] Interestingly, we found that the genetic ablation of STK25 protects mice against NASH‐driven HCC via reduced hepatocellular apoptosis and lowered compensatory proliferation, by a mechanism that involves the suppression of hepatic lipotoxicity and inactivation of liver signal transducer and activator of transcription 3 (STAT3), extracellular signal‐regulated kinase 1/2 (ERK1/2), and p38 signaling—the key pathways implicated in human HCC (Figure 5). [ 96 ] In line with these observations, short hairpin RNA knockdown of STK25 has been demonstrated to inhibit tumor growth in human HCC xenografts in nude mice. [ 97 ] The silencing of STK25 also suppresses proliferation, migration, and invasion in human hepatocarcinoma cells in vitro , which is accompanied by a lower expression of the markers of epithelial–mesenchymal transition (EMT) and augmented autophagic flux.…”
Section: Role Of Gckiii Kinases In Hccmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 95 ] Interestingly, we found that the genetic ablation of STK25 protects mice against NASH‐driven HCC via reduced hepatocellular apoptosis and lowered compensatory proliferation, by a mechanism that involves the suppression of hepatic lipotoxicity and inactivation of liver signal transducer and activator of transcription 3 (STAT3), extracellular signal‐regulated kinase 1/2 (ERK1/2), and p38 signaling—the key pathways implicated in human HCC (Figure 5). [ 96 ] In line with these observations, short hairpin RNA knockdown of STK25 has been demonstrated to inhibit tumor growth in human HCC xenografts in nude mice. [ 97 ] The silencing of STK25 also suppresses proliferation, migration, and invasion in human hepatocarcinoma cells in vitro , which is accompanied by a lower expression of the markers of epithelial–mesenchymal transition (EMT) and augmented autophagic flux.…”
Section: Role Of Gckiii Kinases In Hccmentioning
confidence: 87%
“…[ 97 ] The silencing of STK25 also suppresses proliferation, migration, and invasion in human hepatocarcinoma cells in vitro , which is accompanied by a lower expression of the markers of epithelial–mesenchymal transition (EMT) and augmented autophagic flux. [ 96,97 ] Furthermore, high STK25 expression was found to be correlated with adverse clinicopathological characteristics and poor survival in patients with HCC. [ 97 ]…”
Section: Role Of Gckiii Kinases In Hccmentioning
confidence: 99%
“…DEN is a carcinogen that has been used to induce HCC in different laboratory animal species. [53][54][55] We have previously used DEN in miniature pigs, and found that the histopathological features of the developed HCC resemble to a great extent the human neoplasm. 56 Although etiologically DEN-induced HCC does not mimic this type of cancer in human patients, this model has several important pathological, histological, and biochemical similarities with human HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cell metastasis is one of cancer cells process occurring when primary tumor spread through lymphatic and circulatory system to the nearest organs, as well as is reported to be responsible for over 90% of cancer deaths. Cell migration (motility) is a critical cause of tissue invasion supporting primary tumors to disseminate and metastasize 8 10 . Collective cell migration is mediated by coordinate cytoskeletal activity with cell–cell interaction with neighbor cells and surrounds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liver cancer has been grouping into five stages to prevent medical intervention harms in patients with cirrhosis. Liver cancer metastasis appears in fourth of five stages classify as advanced stage, indicating that the cancer could spread from origin to other organs 8 . For explanation, metastasis occurs when the primary cancer travels from its original place through the bloodstream and lymph node, then forms a secondary or metastatic tumor in the nearest organs.…”
Section: Introductionmentioning
confidence: 99%